Pinedale Deglaciation and Subsequent Holocene Environmental Changes and Geomorphic Responses in the Central Lemhi Mountains, Idaho, U.S.A. - Butler, David (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTIn several glaciated valleys along the eastern front of the Lemhi Mountains, subalpine meadows are located along the central axes of the valleys, in positions immediately upvalley of arcuate Pinedale readvance moraines. The meadows are comprised of varying thicknesses of finegrained sediments which were impounded by the damning action of the moraines. These sediments, and pollen contained therein, record complex environmental fluctuations which accompanied déglaciation and postglacial recovery. The thickness of sediments in each meadow is a function of the proficiency of the arcuate moraines as dams. The presence of Glacier Peak B ash in one meadow illustrates that, at minimum, the lower one-third of that valley was deglaciated prior to approximately 11,250 yr BP. Over one meter of glacial-runoff sediments underlies the ash ; sedimentation rates in the meadow suggest that déglaciation in the lower portions of the valley may have been complete before 11,500 yr BP. Sedimentation rates slowed dramatically after 10,000 yr BP. A cold, early HoIocene climatic episode may have occurred around 7500 yr BP. Massive protalus landforms were deposited during the Indian Basin Advance. Later Neoglacial landforms were areally restricted to the most shaded, climatically-favorable locations.